HOW THE PERCEIVED ENJOYMENT EFFECT M-PAYMENT ADOPTION IN WEST PAPUA PROVINCE: DELONE AND MCLEAN INFORMATION SYSTEMS SUCCESS MODEL - Setiawati, Putri Eka; Inan, Dedi I.; Wurahrah, Rully Novie; Juita, Ratna; Sanglise, Marlinda (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
M-payment is a form of adaptation in payment systems through digital technology. This study aims to determine the influence of perceived enjoyment as a complementary factor to the DeLone and McLean (DM) Information System Success Model of m-payment adoption level in West Papua Province. A total of 244 valid respondents were obtained via a questionnaire using purposive sampling technique and analyzed using PLS-SEM. The results showed that out of eleven hypotheses, eight were accepted, and three were rejected. The result show that the Perceived Enjoyment (PE) significantly influences the m-payment adoption level in West Papua Province. However, service quality is not a determinant of m-payment adoption levels in West Papua Province. Additionally, system quality not a determinant on user satisfaction of the technology. A post-hoc evaluation was also conducted using gender and age as control variables, indicating that the adoption levels varied among the control variable groups. This provides significant insights both theoretical and practical which are discussed in discussion and conclusion section.